Pemanfaatan Media Video dalam Pembelajaran Pembangkit Listrik Tenaga Surya (PLTS) - Muhammad Rivaldan; Meisya Dwi Rizkiana; Sandi Sandi; Arya Bayu Kusuma; Meyrizka Pramayudha; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Technological advancements have brought significant changes to the field of education, particularly in the implementation of learning activities. One of the instructional innovations that has gained widespread adoption is the use of video-based learning media. In vocational education, learning media play an important role in helping students comprehend technical knowledge and practical procedures, especially in the study of Solar Power Plants (PLTS). This article examines the effectiveness of video learning media in PLTS education by analyzing educational content available on YouTube that covers PLTS concepts, system components, operational principles, installation techniques, maintenance procedures, and real-world applications. The study employs a descriptive qualitative approach through observation and content analysis of selected PLTS learning videos. The findings indicate that video media facilitate better student understanding by presenting information in a visual, structured, and contextual manner. In addition, video-based learning enhances student engagement, motivation, and self-directed learning skills. Consequently, learning videos can be considered an effective and innovative educational medium for supporting renewable energy education, particularly in Solar Power Plant learning.